Etiological review and outcome of thrombocytopenia in pregnancy in the tertiary care centre - Desai, Sangeeta S.; Kabade, Kavita S.; T. S. K., Sumitra Reddy; Devireddy, Gheya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Objective of the study was to identify and analyse the etiology of thrombocytopenia in pregnancy and review the evaluation of thrombocytopenia and its outcome in pregnancy. Methods: Retrospective study conducted at D. Y. Patil Hospital, Kolhapur, Maharashtra, India, from January 2021 to January 2023, in the Department of Obstetrics and Gynecology. All the antenatal women admitted in the ward of obstetrics and gynecology with platelet count less than 1 lakh/cubic cc were included in the study. Thorough evaluation for the cause of thrombocytopenia and outcome of the patient were collected and results were analyzed. Results: Out of 3319 deliveries, 100 patients had platelet counts less than 1 lakh. Overall, in the present study, Gestational thrombocytopenia (38%) is the most common cause of low platelets in pregnancy, followed by pre-eclampsia (20%) and DIC (16%). The rest of the etiologies rarely cause thrombocytopenia in pregnancy (<10%). Conclusions: Despite thrombocytopenia is a common abnormality in pregnancy, it seldom leads to life-threatening complications by itself. By contrast, a significant thrombocytopenia associated with medical conditions can have serious maternal-fetal consequences and requires appropriate management. The management of thrombocytopenia focuses on the underlying cause/etiology which is challenging because there are many potential causes, some directly related to the pregnancy and some unrelated. Cause directed therapies, if promptly administered, may significantly improve the maternal and fetal outcomes. Study intended to evaluate the wide spectrum of causes for thrombocytopenia in pregnancy and its outcome. Preeclampsia with or without HELLP syndrome is found to be very important cause of severe thrombocytopenia and attributed with maternal complications. while the perinatal outcome of gestational thrombocytopenia and immune thrombocytopenic purpura is basically favourable.